Gamophobia in Contemporary Society: An Integrative Analysis of Qur’anic Exegesis and Marital Psychology through Tafsir Al-Munir - Nur Hikmah, Ridhani Ayu; Nidhom, Khoirun; Ghifari, Muhammad (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2024)
The rapid transformation of social and cultural values has significantly altered individual perceptions of marriage, leading to the emergence of gamophobia—an excessive fear of marriage and long-term commitment. This phenomenon has become increasingly prevalent among younger generations, influenced by rising divorce rates, economic uncertainty, and media exposure that portrays negative representations of marriage. This study aims to identify the underlying factors contributing to gamophobia and propose Qur’anic-based solutions as interpreted in Tafsir Al-Munir by Wahbah Az-Zuhaili. Using a qualitative approach through library research and thematic exegesis analysis (tafsir maudhu’i), this study examines gamophobia from the perspectives of marital psychology and Islamic studies. The findings reveal three primary factors triggering gamophobia: (1) fear of infidelity due to past experiences of betrayal, (2) concerns about the inability to establish a stable household, and (3) emotional unpreparedness in handling marital conflicts and commitments. Unlike previous studies that predominantly focus on psychological aspects, this research integrates Islamic values as solutions, including choosing a partner with effective conflict resolution skills, practicing tawakkul (trust in Allah) after making efforts, and fostering positive perceptions of divine decree. By employing a multidisciplinary approach that bridges marital psychology and Qur’anic exegesis, this study highlights that gamophobia can be mitigated through a deeper understanding of Islamic teachings, spiritual resilience, and enhanced emotional and mental preparedness for marriage.